Hypothalamic neurogenesis in the adult brain - Cheng, Mei-Fang (Frontiers in neuroendocrinology, 2013)
•Hypothalamic neurogenesis is essential in a functioning energy-balance system.•Role of hypothalamic neurogenesis in adaptive behavior of animals.•The common features of hippocampal, SVZ and hypothalamic neurogenes. Adult-born new neurons are continuously added to the hippocampus and the olfactory bulb to serve aspects of learning and perceptual functions. Recent evidence establishes a third neurogenic niche in the ventral hypothalamic parenchyma surrounding the third ventricle that ensures the plasticity of specific brain circuits to stabilize physiological functions such as the energy-balance regulatory system. Hypothalamic lesion studies have demonstrated that regions associated with reproduction-related functions are also capable of recruiting newborn neurons to restore physiological functions and courtship behavior. Induced by lesion or other stimulation, elevated neurotrophic factors trigger neurogenic cascades that contribute to remodeling of certain neural circuits to meet specific transient functions. This insight raises the possibility that event-specific changes, such as increased GnRH, may be mediated by courtship-sensitive neurotrophic factors. We will discuss the potentially integral and ubiquitous roles of neurogenesis in physiological and biological phenomena, roles that await future experimental exploration.